Research on the Influence of Chinese Social Media on Women’s Self-esteem Catalyzed by the Homogenization of Female Images in China - Piao Xiumin (SHS Web of Conferences)
Social media in modern society are platforms where everyone can present themselves, and they are also “stages” where women can present diverse images of women and convey messages of women’s strength. Most of the images of women are from a male aesthetic perspective, and men’s discourse in the image of women is higher than that of women. Nowadays, the status of women in Chinese society is gradually rising, but women still do not have a great say in image aesthetics. This phenomenon is particularly evident in social media platforms, where women’s aesthetic shift towards diversity has significant limitations and fails to break free from restrictive aesthetic frameworks, leading to the problem of women’s self-esteem being undervalued. Numerous advertisers market and pursue commercial gain by selling anxiety and constantly instilling the idea that the value of women depends on the image of female beauty. Social media platforms need to guide women to the correct concept of aesthetics, and the government and legal authorities need to formulate relevant laws and guide correct values to enhance women’s sense of self-esteem and promote a more diversified aesthetic and the concept of a healthy and beautiful image.